How Early Life Adversity Influences Defensive Circuitry - Murthy, Sahana (Trends Neurosci, 2020)
Childhood maltreatment increases the likelihood of developing anxiety disorders in humans. Early life adversity (ELA) paradigms in rodents produce lasting increases in avoidant and inhibitory responses to both immediate and nonspecific threats, collectively referred to as defensive behaviors. This approach provides an opportunity to thoroughly investigate the underlying mechanisms, an effort that is currently under way. In this review, we consider the growing literature indicating that ELA alters the rhythmic firing of neurons in brain regions associated with defensive behavior, as well as potential neuronal, glial, and extracellular matrix contributions to functional changes in this circuitry. We also consider how ELA studies in rodents may inform us about both susceptible and resilient outcomes in humans.